The Evaluation of Multiple Birth Rates For Patients Who Had IVF-ET Procedure in Our Clinic - Duru, Namık Kemal; Gezginç, Kazım; Karaşahin, Emre; Alanbay, İbrahim; Fidan, Ulaş; Başer, İskender (Gynecology Obstetrics & Reproductive Medicine, 2008)
OBJECTIVE: We evaluated the multiple birth rates for the patients who had undergone IVF-ET procedure in our clinic. STUDY DESIGN: Total number of births and the amount of the births following assisted reproductive techniques (ART) in 2006 in Gulhane Military Medical Academy was investigated. We determined the multiple pregnancy rates among the total births, and our overall success rates, and compared those with the embryo transfer policies and the multiple pregnancy rates of other countries. RESULTS: 120 out of 1797 births (6.6%) in 2006 was the result of ART. A total of 345 embryo transfers made resulted in 176 pregnancies (51%). Live birth rate per embryo transfer was 35%, (120/345). Multiple births were 42 (2.5%), and all were the result of the ART. The ratio of multiples in ART pregnancies were 35%, (42/120). CONCLUSION: Elective single embryo transfer should be promoted by explaining the patients the possible complications of the multiple pregnancies in detail.